A conceptual model for improving outcomes on student teams through the selection process. (21st September 2021) - Crowne, Kerri Anne; McCloskey, Donna Weaver
The aim of this article is to present a conceptual model of the positive individual and team outcomes that exist from student teams being actively involved in the team formation. It builds on a previously published teaching activity that outlined a team selection process in which students anonymously reviewed potential teammate's resumes. By having students select teammates through a resume-based simulated hiring process, students reflect on the project needs and the requisite skills needed. Using a simulated hiring activity is particularly relevant for business students, since reviewing resumes is usually the first step in the hiring process, thus business students in higher education are learning a necessary skill for their future careers. This article provides additional support for instructors to use an alternative method of team formation that should create more effective teams.